Model AIDA: Pola Penggunaan Media Sosial dalam Meningkatkan Kepuasan Penjualan di Toko Online Goldies Hijab - Poetra, Reza Riesnanda; Christantyawati, Nevrettia (Jurnal Komunikasi Profesional, 2017)
This research would to answer the following research questions: how the patterns of use of social media in increasing sales satisfaction in the online store goldies hijab?      This research data overall obtained and collected through questionnaires, observation and documentation (written data) which was then analyzed using descriptive statistical methods then the conclusions drawn through quantitative techniques, with deductive mindset. The results of this study concluded:      First, when seen from awerness, patterns of use of social media to increase sales satisfaction in the online store goldies hijab in the category of neutral 50 respondents or 50%, this is because the pattern of use of social media has had a negative impact on importers and positive impact on the seller for profit ride. While as many as 45 respondents or 45% categorized as positive as negative impact if done. And as much as 5 or 5% of respondents categorized as negative, because the pattern of use of social media does not have a negative impact if not done.      Second, when seen from the interest, the pattern of use of social media to increase sales satisfaction in the online store goldies hijab in the category neuter as many as 40 respondents or 40%, this is because the pattern of use of social media has a negative impact on the material or materials production and positive impact on production as orders increase. While as many as 55 respondents or 55% categorized as positive as negative impact if done. And as much as 5 or 5% of respondents categorized as negative, because the pattern of use of social media does not have a negative impact if not done.      Third, when seen from the desire, the pattern of use of social media to increase sales satisfaction in the online store goldies hijab in the category of neutral as much as 65 respondents or 65%, this is because the pattern of use of social media has had a negative impact on the desire to have a product and a positive impact on menjul desire a product. While as many as 33 respondents or 33% categorized as positive as negative impact if done. And as much as 2 or 2% of respondents categorized as negative, because the pattern of use of social media does not have a negative impact if not done.      Fourth, when viewed from the action, media usage patterns sosialdalam increase sales satisfaction in the online store goldies hijab. In the neutral category by 56 respondents or 56%, this is because the pattern of use of social media has had a negative impact on the actions of buyers and positive impact on the selling action. While as many as 44 respondents or 44% categorized as positive as negative impact if done. And as much as 0 or 0% of respondents categorized as negative, because the pattern of use of social media does not have a negative impact if not done.Keywords: AIDA, Online Marketing, Social Media